Integrating softwood biorefinery lignin into polyhydroxybutyrate composites and application in 3D printing. (June 2019) - Vaidya, Alankar A.; Collet, Christophe; Gaugler, Marc; Lloyd-Jones, Gareth
Graphical abstract: Highlights: Melt extrusion blending of softwood biorefinery lignin with PHB, a bioplastic polymer. Characterization of composite showed biorefinery lignin as a non-reactive filler. Reduced warping of 3D printed PHB composite on addition of 20% biorefinery lignin. Abstract: The massive volumes of residual lignin that will be generated as a biorefinery industry by-product provide an opportunity for bio-composite manufacture. In this context, biorefinery lignin produced from the saccharification of Pinus radiata wood pulp without any further derivatization or coupling or chemical modifications was blended and melt extruded with polyhydroxybutyrate (PHB) to form composite filaments. The filaments were cut into pellets and compression moulded into films. The pellets/films were characterised by FTIR, SEM, 13 C NMR, water contact angle, TGA and DSC. The FTIR and SEM analyses suggested a particulate polymer composite in which filaments have a PHB-rich surface and discrete lignin particles contained within the filament core. The 13 C NMR spectroscopy showed the proportion of phenolic carbon signal associated with aromatic moieties in lignin increased with the proportion of the biorefinery lignin added into the composite. The decomposition, melting and crystallization temperature of PHB polymer did not appreciably change after the inclusion of biorefinery lignin into the composite. The PHB composite containing biorefinery lignin had a shear thinning profile which enhanced layer adhesion during 3D printing. The water contact angle of the moulded films was increased with the addition of the biorefinery lignin indicating lignin exerted a hydrophobic effect on the PHB films. The rheology results indicate that lignin when added as a filler at 20% w/w changes melt viscosity and is conducive for 3D printing. Hence, as an example of the additive manufacturing, the extruded composite filament with 20% biorefinery lignin was 3D printed and showed between 34 to 78% less warpage compared to the 100% PHB printed object. Incorporating biorefinery lignin into 3D printed PHB filaments represents a potential application for valorising softwood biorefinery lignin.